Stability, correlation and path analysis for seed yield and yield-attributing traits in clusterbean (Cyamopsis tetragonoloba) - PATHAK, RAKESH; SINGH, MANJIT; HENRY, A (The Indian Journal of Agricultural Sciences, 2011)
Stability parameter, correlation and path analysis were studied during rainy (kharif) seasons of 2005, 2006 and 2007 among 40 genotypes of clusterbean [Cyamopsis tetragonoloba (L.) Taub.] for yield-related characters. The genotype×environment interaction was highly significant for all the traits studied and a large portion of the interaction was accounted for by the linear components for all the traits. ‘CAZG 6’, ‘RGC 1029’, ‘GAUG 003’, ‘GAUG 005’, ‘RGC 1002’, ‘HGS 880’, ‘CAZG 50’, ‘RGC 1030’, ‘RGM 114’, ‘WSP 50’, ‘HGS 02-1’ and ‘CLBH 201’were stable for favourable environments while ‘VIKAS 35’, ‘RGC 1038’, ‘RGC 1076’ and ‘GAUG 004’ were better performing and stable under unfavourable environment for seed yield and yield-attributing traits. The highest correlations were found with seed yield and pods/plant (r = 0.89), seeds/pod (r = 0.53), secondary branches/plant (r = 0.49), plant height (r = 0.48) and primary branches/plant (r = 0.29). Path analysis indicated the highest direct and positive effect of pods/plant (0.85), seeds/pod (0.28) and 100-seed weight (0.23) on seed yield. The study validates that the number of pods and number of branches are important characters for improvement of seed yield in clusterbean.